Application of Collagen I and IV in Bioengineering Transparent Ocular Tissues - Song, Yihui; Overmass, Morgan; Fan, Jiawen; Hodge, Chris; Sutton, Gerard; Lovicu, Frank J.; You, Jingjing (Frontiers in Surgery, 2021)
Collagens represent a major group of structural proteins expressed in different tissues, and display distinct and variable properties. Whilst collagens are non-transparent in skin, it confers transparency in the cornea and crystalline lens of the eye. There are 28 types of collagen that all share a common triple helix structure, yet differ in the composition of their α-chains. These differences lead to the different properties, and organization of collagen fibres that contribute to the different morphologies of tissues. The important role of collagen in forming different tissues has led to the exploration and application of collagen as a biomaterial. Collagen I and collagen IV are the two main collagens in the cornea and lens, respectively, involved in tissue transparency, essential for vision. The visual light pathway involves the focusing cornea, the accommodative, focussing lens and photoreceptive neural retina. This review explores the application of these two collagen types as novel biomaterials in bio-engineering unique transparent tissues that could be used to treat various forms of blindness.